Services Export and Economic Growth in ASEAN Countries. Issue 2 (September 2019) - Sermcheep, Sineenat
Abstract: Based on the panel data from 1980 to 2014, this article examines the effect of services export on economic growth in the ASEAN countries. The results show that there has been evidence of services export-led growth in ASEAN during the past decades. The services export data are disaggregated into modern and traditional services exports, and the estimations show that both exports contribute to the GDP growth with the less strong positive effect from the modern services exports. The goods export, conventional engine of growth, also maintains its significant and robust role as the growth-enhancing factor for ASEAN. In the period of a slow growth of goods exports and the direction of the growth policy towards services-oriented sector, the services exports have become increasingly significant as a new engine of growth, which also complement to the existing growth engine. JEL Codes: F43, O4